Effects of Artificial Intelligence on the Academic Performance of Grade Six Pupils - Goto, Joana Marie (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effects of Artificial Intelligence (AI) on the academic performance of Grade Six pupils in selected public elementary schools in the District of Binangonan, Division of Rizal, School Year 2025–2026. It employed a descriptive survey research design complemented by documentary analysis of pupils’ quarterly grades. A total of 352 respondents were selected from 2,042 Grade Six pupils using Slovin’s formula and simple random sampling. Data were gathered through a researcher-made questionnaire-checklist measuring AI’s perceived effects in terms of motivation, class engagement, lesson mastery, and critical thinking and problem solving. Academic performance was determined using first and second quarter grades. Findings revealed that most respondents were 12 years old, female, firstborn, and from low-income families. Parents were generally high school to college graduates, with varying occupations, and pupils reported occasional use of AI tools. Results indicated that AI has a high perceived effect on pupils’ motivation, engagement, lesson mastery, and critical thinking skills. No significant differences were found in the perceived effects when grouped according to age, sex, number of children in the family, father’s educational attainment, and monthly family income. However, sibling position, mother’s educational attainment, parents’ occupation, and frequency of AI use showed significant differences. Pupils demonstrated a Very Satisfactory level of academic performance. Moreover, no significant positive relationship was found between perceived AI effects and academic performance. The study concludes that AI meaningfully influences learning processes but does not directly translate to higher academic performance. It recommends the formulation of school policies on AI integration, teacher training on instructional alignment, parental guidance, and responsible pupil use of AI as a learning support tool. Future researchers are encouraged to explore additional variables and conduct longitudinal studies to further validate these findings across diverse learning contexts and improve AI integration practices in basic education in the Philippines.
Keywords: Artificial Intelligence, academic performance, Grade Six pupils, descriptive survey, documentary analysis, AI Tools